Metode Convolutional Neural Network Dalam Klasifikasi Citra Tiga Tokoh Wayang Pandawa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Puppet Show is a traditional Indonesian drama, where Pandawa is one of the stories that is often shown. Pandawa is the story about five siblings who received unfair treatment from his ancle and cousin. When they succeeded in defeating his cousin, they still honored his uncle as a family. Each story in a Puppet Show has a very useful message in life, such as the story of Pandawa. Although many times attempted to be destroyed by another family, they never gave up. Until finally they can have what they are supposed to belong to. Nowadays, Puppet Show is increasingly forgotten because of technology development. This research aims to help preserve Puppet Show, by creating programs that can help in identifying puppet figures using machine learning. Machine learning is a learning process that learns data based on historical data. The Convolutional Neural Network (CNN) is a method in machine learning that can be used to create training models to classify data consisting of more than two classes. The characters to be classified in this research are Yudhistira, Bima and Arjuna. The Total data used is 600 which is 100 × 100. By using Softmax activation function for classifying its class, the accuracy obtained is 96,67%. Keywords: Convolution Neural Network, Classification, Pandawa, Puppet Show